2014
DOI: 10.1038/nnano.2014.100
|View full text |Cite
|
Sign up to set email alerts
|

Multi-enzyme complexes on DNA scaffolds capable of substrate channelling with an artificial swinging arm

Abstract: The general design of the swinging arm nanostructure complex is shown in Fig. 1a, where a two-enzyme cascade consisting of glucose-6 phosphate dehydrogenase (G6pDH) 19 and malic dehydrogenase (MDH) 20 is displayed on a DNA double-crossover (DX) tile scaffold 21 (DNA sequences for all structures used in this study are shown in Supplementary Figs. S1-S7).G6pDH catalyzes the oxidation of glucose-6-phosphate and the reduction of NAD + to NADH.Subsequently, MDH catalyzes the reduction of oxaloacetate to malic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
419
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 439 publications
(435 citation statements)
references
References 26 publications
8
419
0
2
Order By: Relevance
“…They were able to control the enzymatic activity by opening and closing the tweezers using additional DNA oligonucleotides as fuel. Fu et al [58] fabricated multienzyme cascades on DNA templates, where substrate channeling was realized using a DNA strand as a flexible swinging arm between the immobilized enzymes. Linko et al [59] showed how modular DNA origami building blocks could be assembled together to form a tubular enzyme cascade nanoreactor ( Figure 2C) for detecting glucose.…”
Section: Smart Dna Nanodevices and Molecular Platformsmentioning
confidence: 99%
“…They were able to control the enzymatic activity by opening and closing the tweezers using additional DNA oligonucleotides as fuel. Fu et al [58] fabricated multienzyme cascades on DNA templates, where substrate channeling was realized using a DNA strand as a flexible swinging arm between the immobilized enzymes. Linko et al [59] showed how modular DNA origami building blocks could be assembled together to form a tubular enzyme cascade nanoreactor ( Figure 2C) for detecting glucose.…”
Section: Smart Dna Nanodevices and Molecular Platformsmentioning
confidence: 99%
“…Early in 1980s, Mansson and co-workers 87 immobilized the lactate dehydrogenase (LDH) and alcohol dehydrogenase (ADH) on agarose beads with the aid of a bis-NAD analogue, followed by glutaraldehyde cross-linking to achieve an orientation of enzymes facing their active sites to each 24 Artificial swinging mediator for intermediate channeling.In the enzymatic reaction with cofactors involved, transportation of cofactors sometimes determines the overall activity. Very recently, Fu and colleagues78 presented an ingenious multi-enzyme-DNA complex by employing a swinging arm modified with NAD + on its terminal to mimic the substrate channeling (Figure 6). The swinging arm placed between the glucose-6-phosphate dehydrogenase (G6pDH) and malic dehydrogenase (MDH) facilitated the channeling of NADH/NAD + between the two enzymes.…”
mentioning
confidence: 99%
“…Inspired by nature, NAD(P)H and enzymes have been co‐immobilized on solid materials allowing their solid‐phase recycling and reusability for several operational cycles 3a, 4. These heterogeneous systems, however, have shown several drawbacks; the enzymatic activity towards the immobilized cofactors is low,5 the turnover numbers of the immobilized cofactors are poor (≤1),6 the re‐usability of both enzymes and cofactors is limited5, 7 and the fabrication of these systems is hardly scalable 8. However, the use of strong and non‐porous anionic exchangers has shown that the cofactor re‐utilization works in organic media9 but fails in aqueous media owing to the lixiviation of both NAD(P)H and enzymes from the matrix 10.…”
mentioning
confidence: 99%